Coproparasitological diagnosis of Fasciola hepatica in cattle in a cuban livestock farm - Godoy M., Yuraimis (2010)
The aim of the study was to compare the coproparasitological method of Benedek sedimentation against the immunoenzimeassay for the diagnosis of Fasciola hepatica in cattle from a Cuban livestock large farm. A descriptive cross-sectional study was conducted in February-March 2008 and faecal samples were collected to 254 Jersey, Holstein, and crossbreed animals. Sixteen positive cases (6.3%) were detected using FasciDIG whereas only 10 (3.9%) using the Benedek sedimentation method. It was concluded that the immunoassay method (FasciDIG) showed better diagnostic sensitivity than the Benedek sedimentation test.